Second Order Duality for Minmax Fractional Programming Problem Involving (F,...,d)-Type I Functions - Jayswal, Anurag; StancuMinasian, Ioan; Ahmad, I (Bulletin of the Malaysian Mathematical Sciences Society, 2014)
In this paper, we focus our study on a minmax fractional programming problem and its second order dual. Weak, strong and strict converse duality theorems are established assuming the involved functions to be second order ...- type I. 2010 Mathematics Subject Classification: 26A51, 49J35, 90C32 (ProQuest: ... denotes formulae omitted.)